Optimalisasi Regulasi dan Perlindungan Investor Terhadap Investasi Bodong di Pasar Modal Syariah - Putri, Amelia Juliana; B, Baidhowi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Islamic capital market is currently growing rapidly as an investment alternative that is in accordance with Islamic principles. However, this growth is also accompanied by the rampant cases of fraudulent investments that harm investors and threaten the credibility of the Islamic capital market. This article discusses the challenges of regulation and strategies for optimizing investor protection in dealing with fraudulent investments in the Islamic capital market. Using a juridical-normative approach, this study analyzes the applicable regulations, weaknesses in supervision, and prevention efforts that have been carried out by relevant authorities such as the Financial Services Authority (OJK), the Indonesia Stock Exchange (IDX), and the National Sharia Council-Indonesian Ulema Council (DSN-MUI). The results of the study indicate that although Islamic capital market regulations in Indonesia have developed, there are still gaps in supervision and investor protection mechanisms, especially in terms of early detection and law enforcement against illegal investments. Therefore, it is necessary to optimize regulations by strengthening supervision mechanisms, increasing Islamic financial literacy, and utilizing technology such as Regulatory Technology (RegTech) in detecting and preventing fraudulent investments. With these steps, it is expected that the Islamic capital market can be more trusted, transparent, and able to provide better protection for investors.